Characterization of Group C Rotaviruses Associated with Diarrhea Outbreaks in Feeder Pigs - Kim, Yunjeong (American Society for Microbiology, 1999)
Feces and serum specimens were collected from three farms in Michigan on which ∼50-lb (8- to 9-week-old) pigs experienced diarrhea just after placement into all-in-all-out finishing barns. The clinical signs (profuse watery diarrhea lasting about 2 weeks and no vomiting) were similar on all farms, and the morbidity rate was high (ranging from 60 to 80%) but without mortality. Eleven diarrheic fecal samples from the farms were tested for group A and C rotaviruses by immune electron microscopy (IEM) and various assays. IEM indicated that the fecal samples reacted only with antiserum against group C rotaviruses, and polyacrylamide gel electrophoresis indicated that the samples had characteristic genomic electropherotypes for group C rotavirus. Group C rotavirus was detected by cell culture immunofluorescence (CCIF) tests in nine fecal samples, but no group A rotavirus was detected by enzyme-linked immunosorbent assay or CCIF. By reverse transcription (RT)-PCR, all 11 fecal samples were positive for group C rotaviruses, with only 2 samples positive for group A rotaviruses. However, a second amplification of RT-PCR products using nested primers detected group A rotaviruses in all samples. Analysis of nucleotide and deduced amino acid sequences of the RT-PCR product (partial-length VP7) of the group C rotavirus showed 87.2 to 91% nucleotide identity and 92.6 to 95.9% amino acid identity among two strong samples from the different farms and the Cowden strain of porcine group C rotavirus. All nine convalescent-phase serum samples tested had neutralizing antibodies to the Cowden strain, and the majority of them had neutralizing antibody against group A rotaviruses (OSU or/and Gottfried strains) by fluorescent focus neutralization tests. Although group C rotaviruses have been reported as a cause of sporadic diarrhea in suckling or weanling pigs, to our knowledge, this is the first report of epidemic diarrhea outbreaks associated with group C rotavirus in older pigs.